Analisis Tingkat Kesehatan Bank Dengan Menggunakan Metode Camel Pada Bank Syariah Indonesia - Aliyah, Silvia Nur; A'yun, Inarotul (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
The bank's health level is very important to maintain because it is an institution that relies on the trust of its customers. This study aims to describe Bank Syariah Indonesia's health level in the quarter of July 2022-September 2023. The method used in this study was the CAMEL method. The CAMEL method is a specific method in financial statements, the CAMEL method consists of several aspects, namely Capital, Asset, Management, Earning, and Liquidity. The results of this research that Bank Syariah Indonesia in the quarter of July-September 2022 received a value of 96.13%, the quarter of October-December 2022 with 95.8%, the quarter of January-March 2022 with 95.88%, the quarter of April June 2023 with a value of 95.78% and the quarter of July-September 2023 with a value of 95.89%. Based on Bank Indonesia guidelines, healthy banks are banks that have a value of 81-100%, so Bank Syariah Indonesia in the quarter of July 2022-September 2023 is in the category of healthy banks. From the results of the research, it can be concluded that the level of Bank Syariah Indonesia in the quarter of July 2022 September 2023 is included in the category of healthy banks. The results of this study are expected to be the basis and comparison with the latest methods.